Analisis Strategi Komunikasi Digital Affiliator Pemasaran Fashion dan Beauty di Shopee - Al Haq, Tata Wine; Supratman, Lucy Pujasari (Ranah Research : Journal of Multidisciplinary Research and Development, 2024)
This research was conducted to find out the digital communication strategy that Affiliators have in marketing in the field of fashion and beauty on shopping sites on social media Instagram. Shopee is an e-commerce platform that offers online buying and selling transactions safely and reliably via cellphones. Shopee is the object of this research because Shopee has succeeded in marketing digitally to Indonesian consumers, one of which is its Shopee Affiliate program. In this study, we want to examine Affiliators who play a role in promotional activities where someone will sell other people's products and get a commission if a purchase occurs through our reference. This research uses an interview method with 9 active affiliates on Instagram social media. Based on the results of the analysis, there are two most dominant concepts in communication attractiveness, namely Rational and Emotional Attractiveness, while social media influencers have two high source credibility attitudes, namely Attractiveness and Trustworthiness.